If you decide to go to the moon - McNulty, Faith. (Scholastic, 2005)
"If you decide to go to the moon," writes Faith McNulty, "read this book first. It will tellyou how to get there and what to do after youland. The most important part tells you how to get home. Written in the second person, the text allows the reader to participate in every aspect of the journey, from packing ("don't forget your diary and plenty of food") to liftoff (at first you'll feel heavy; don't worry") to traveling thorugh space (where "the moon glows like a pearl in the black, black sky"). The reader lands at the Sea of Tranquility, the site of the first lunar landing